BULL'S EYE MACULOPATHY WITH MUTATIONS IN RDS/PRPH2 AND ROM-1. (2018) - Essilfie, Juliet O.; Sanfilippo, Christian J.; Sarraf, David
Abstract : Purpose: To report a case of bull's eye maculopathy associated with mutations in RDS/PRPH2 and ROM-1 genes. Methods: We present a case report of a patient with a characteristic maculopathy and describe the multimodal retinal imaging findings including spectral domain optical coherence tomography and fundus autofluorescence and full-field electrophysiology. The results of genetic testing are also reported. Results: A 60-year-old woman presented with decreased vision and a remarkable bull's eye maculopathy with retinal examination. Fundus autofluorescence illustrated a striking pattern of speckled hyperautofluorescence and hypoautofluorescence that highlighted the bull's eye maculopathy in each eye and guided genetic testing, which confirmed a mutation of the RDS/PRPH2 gene and a novel mutation of the ROM-1 gene. Conclusion: Multimodal imaging including fundus autofluorescence may guide genetic testing in patients with a characteristic maculopathy. RDS/PRPH2 genetic mutation can be associated with a bull's eye maculopathy with a signature fundus autofluorescence presentation. Abstract : The authors present a case of bull's eye maculopathy with characteristic fundus autofluorescence findings associated with mutations in RDS/PRPH2 and ROM-1 genes.